2015
DOI: 10.5546/aap.2015.eng.158
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes mellitus: psychosocial factors and adjustment of the pediatric patient and his/her family. Review

Abstract: Type 1 diabetes mellitus is the most common chronic endocrine disease in children, with a very low incidence in the first months of life and reaching its peak during puberty (10-15 years old is the age group with the highest incidence at the time of onset). Based on the review of the scientific literature, our objective is to study the main psychosocial factors associated with the adjustment of these pediatric patients and their families. Research underscore the following risk factors: situational (stressful l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Famílias equilibradas, coerentes e organizadas apresentam melhor bem-estar, e menor nível de ansiedade e depressão, mais energia, melhor gerenciamento do diabetes e menos probabilidade de ocorrência de conflitos (Pérez-Marín et al, 2015) Por sua vez, em uma estrutura familiar fragilizada, a necessidade de tomar decisões diárias pelo paciente e a falta de adaptação à doença pode fazer com que a família sofra impactos negativos no bem-estar psicológico, desenvolvendo sintomas e doenças como estresse e/ ou depressão, condições que estão frequentemente associadas a níveis glicêmicos descompensados (Zurita-Cruz et al, 2017;Albuhairan et al, 2016).…”
Section: Participação Da Família No Cuidadounclassified
“…Famílias equilibradas, coerentes e organizadas apresentam melhor bem-estar, e menor nível de ansiedade e depressão, mais energia, melhor gerenciamento do diabetes e menos probabilidade de ocorrência de conflitos (Pérez-Marín et al, 2015) Por sua vez, em uma estrutura familiar fragilizada, a necessidade de tomar decisões diárias pelo paciente e a falta de adaptação à doença pode fazer com que a família sofra impactos negativos no bem-estar psicológico, desenvolvendo sintomas e doenças como estresse e/ ou depressão, condições que estão frequentemente associadas a níveis glicêmicos descompensados (Zurita-Cruz et al, 2017;Albuhairan et al, 2016).…”
Section: Participação Da Família No Cuidadounclassified
“…Avoidant strategies have been connected to worse metabolic control and poorer psychological outcomes, such as lower quality of life and social competence, and greater depressive symptoms, while seeking social support and utilizing humor have been linked to better metabolic control [23][24][25]. The literature showed that coping strategies represent protective factors in adapting to T1D: problem-focused strategies are more useful for situations that can be modified, and emotion-focused coping in unchangeable ones [26]. Moreover, coping skills training interventions seem to be effective in the psychological adjustment to the disease and its management [24].…”
Section: Introductionmentioning
confidence: 99%
“…The management of the disease is complex causing a high burden in the people with T1D daily life and affecting adhesion to treatment. Consequently, a high proportion of them doesn’t achieve the intended targets and are at higher risk of developing complications and of having early mortality [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%